Sexual selection maintains a female-specific character in a species with dynamic sex roles. (25th March 2021) - Hare, Robin M; Simmons, Leigh W
Abstract: The effects of sexual selection are more conspicuous among male animals, and, as a result, the majority of sexual selection research focuses on males. However, burgeoning evidence suggests that sexual selection also acts on females, and there have been calls for an increased focus on females. Here, we used a multivariate approach to analyze sexual selection in Kawanaphila nartee, a spermatophore gift-giving bushcricket with dynamic sex roles. Early in the breeding season, females compete for males, and, later, when environmental food resources are more abundant, sex roles revert to Darwinian convention. Ear size, which is much greater in females than in males, has been suggested to affect female fitness as females with larger ears are more likely to reach calling males first under sex-role-reversed conditions. We tested this suggestion and found evidence of positive linear and nonlinear correlational selection acting on female ear size early in the breeding season (under reversed sex roles) but not later in the breeding season (under Darwinian sex roles). Interestingly, there was no correlation between mating success and reproductive success (Bateman gradient) at any time during the season. Together, our results indicate that even brief and circumscribed periods of intrasexual competition among females can lead to sexual selection on morphological characters and that this selection may not depend on multiple mating. Considering the wealth of reports in the literature of brief episodes of intrasexual competition among female animals, we recommend increased study of sexual selection acting on females. Abstract : When we think of animals competing for a mate, we usually picture vibrant or vigorous males. But females compete too. We examined female–female competition for matings in an insect where sometimes males compete and sometimes females compete. We found that large female ear size, essential for finding singing males, is maintained by the pressure of female–female competition for mates. This shows that competition affects females just as it does males.